Population Ecology and Habitat use of the Sea Slug Elysia pusilla (Bergh, 1872) (Sacoglossa) in A Tropical Halimeda macroloba Decaisne Meadow - Nakpan, Apisara; Mayakun, Jaruwan; Wangkulangkul, Kringpaka (Trends in Sciences, 2022)
Relationship between abundance of specialist marine herbivores and their food sources is poorly known because these herbivores are relatively rare in marine systems. The relationship between the cryptic sea slug Elysia pusilla (Bergh, 1872) and its host alga, Halimeda macroloba Decaisne, was evaluated in terms of spatial association and habitat utilization in a tropical algal meadow in southern Thailand that exclusively comprised of H. macroloba. The density of H. macroloba and of E. pusilla egg masses varied temporally throughout the sampling period, but temporal variation was not detected in the density of E. pusilla individuals, which was generally low with a maximum of 4 individuals per 400 cm2. Analysis suggests that the occurrence of the slug and its egg masses might be determined by the availability of the algal host. The slug was more likely to be observed in dense patches of algae that which offered a large total algal surface area. Occurrence of the slug was also higher when the algae were abundant. The numbers of slugs, egg masses and grazing marks were higher on mature thalli, which have larger surface areas than younger thalli. Egg masses and grazing marks were observed more often on segments at terminal positions on thalli. According to previous works, these segments contain low levels of accumulated calcium carbonate and high levels of secondary metabolites, which are sequestered by the slug and used to deter predators. The findings provide an insight into the life history of E. pusilla and variations in a natural population which that were previously little known. HIGHLIGHTS The relationship between the cryptic sea slug Elysia pusilla (Bergh, 1872) and its host alga, Halimeda macroloba Decaisne, was evaluated in terms of spatial association and habitat utilization in a tropical algal meadow in southern Thailand The slug pusilla was more likely to be observed in dense patches of its algal host H. macroloba Occurrence of the slug was also higher when the algae were abundant The numbers of slugs, egg masses and grazing marks were higher on mature thalli Egg masses and grazing marks were observed more often on segments at terminal positions on thalli GRAPHICAL ABSTRACT